2002
DOI: 10.1046/j.1462-2920.2002.00294.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogenetic analyses of reverse‐transcribed bacterial rRNA obtained from deep‐sea cold seep sediments

Abstract: A depth profile of naturally occurring bacterial community structures associated with the deep-sea cold seep push-core sediment in the Japan Trench at a depth of 5343 m were evaluated using molecular phylogenetic analyses of RNA reverse transcription-PCR (RT-PCR) amplified 16S crDNA fragments. A total of 137 clones of bacterial crDNA (complimentary rDNA) phylotypes (phylogenetic types) obtained at three different depths (2-4, 8-10 and 14-16 cm) were identified in partial crDNA sequencings. crDNA phylotypes fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 56 publications
(79 reference statements)
4
58
0
1
Order By: Relevance
“…In addition to sulfate reducers, chemolithoautotrophic sulfur oxidizers, such as members of the Epsilonproteobacteria, were detected in the RNA-based sequence library constructed from sample collected at the top of the sediment. The reduced sulfur compounds may support some sulfur oxidizers (Inagaki et al, 2002(Inagaki et al, , 2003 that were not detected in the deeper sediment, possibly owing to the lack of available electron acceptors (for example, O 2 and nitrate) in the CO 2 -rich low-pH sediment. The seafloor sediment in the Yonaguni Knoll IV hydrothermal field harbors a remarkable number and diversity of microbes (Inagaki et al, 2006;Nunoura and Takai, 2009;Nunoura et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
“…In addition to sulfate reducers, chemolithoautotrophic sulfur oxidizers, such as members of the Epsilonproteobacteria, were detected in the RNA-based sequence library constructed from sample collected at the top of the sediment. The reduced sulfur compounds may support some sulfur oxidizers (Inagaki et al, 2002(Inagaki et al, , 2003 that were not detected in the deeper sediment, possibly owing to the lack of available electron acceptors (for example, O 2 and nitrate) in the CO 2 -rich low-pH sediment. The seafloor sediment in the Yonaguni Knoll IV hydrothermal field harbors a remarkable number and diversity of microbes (Inagaki et al, 2006;Nunoura and Takai, 2009;Nunoura et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
“…The growth temperature ranges and the ability to utilize hydrogen or oxygen of these genera might fit with the geochemical settings of indigenous habitats. We have previously reported that members of e-proteobacterial group F coexist with sulfate reducers within the d-Proteobacteria in deep-sea cold seep environments (Inagaki et al, 2002). Mesophilic sulfur-oxidizing bacteria phylogenetically related to isolate 42BKT T might contribute to sulfur (re)cycling in global deep-sea environments.…”
Section: Phylogenetic Position and Ecological Significancementioning
confidence: 98%
“…3). Group F contains large numbers of environmental sequences obtained from deep-sea hydrothermal systems (Reysenbach et al, 2000;Teske et al, 2002) and cold seep environments (Li et al, 1999;Inagaki et al, 2002) (Fig. 3).…”
Section: Phylogenetic Position and Ecological Significancementioning
confidence: 99%
“…Sediment depth-related patterns in bacterial community structure were, for instance, detected for a variety of benthic habitats, such as cold seep sediments (Inagaki et al, 2002), the warm deep Mediterranean sea (Luna et al, 2004), the western Pacific coast (Urakawa et al 2000), the Antarctic continental shelves (Bowman and McCuaig, 2003), coral reef sediments , as well as for continental shelf sediments of the southern North Sea (Franco et al, 2007).…”
Section: Introductionmentioning
confidence: 99%